2016
DOI: 10.3109/17549507.2016.1159335
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the emerging profession of speech-language pathology in Vietnam through pioneering eyes

Abstract: Participants' reflections draw focus to an important role for the international SLP community as it works in partnership with colleagues to enhance awareness of and services for people with communication disabilities in under-served communities such as Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This research was similar to others in that it showed speech therapists had modest levels of job satisfaction [11]. The results are in agreement with earlier research; in which speech therapists saw their correlations with job satisfaction [12].…”
Section: Discussionsupporting
confidence: 92%
“…This research was similar to others in that it showed speech therapists had modest levels of job satisfaction [11]. The results are in agreement with earlier research; in which speech therapists saw their correlations with job satisfaction [12].…”
Section: Discussionsupporting
confidence: 92%
“…Data were collected from children in Ho Chi Minh City, and not other areas of Southern Viet Nam. While the sample (n = 132) was slightly smaller than the sample gathered in Northern Viet Nam (n = 195) (Phạm & McLeod, 2019), these data contribute to foundational knowledge for the emerging speech-language pathology profession in Viet Nam (Atherton, Davidson, & McAllister, 2017). It would be useful to gain data from more children with a wider range of ages (beginning with 2-year-old children) from other areas of Southern Viet Nam who speak the Southern Vietnamese dialect, as well as from Central Vietnam.…”
Section: Limitations and Future Directionsmentioning
confidence: 79%
“…However, the very concept of profession remains much disputed (Sciulli, 2005;Evetts, 2013). For instance, identities happen to emerge in fields where professions do not have certifications and credentials (Armstrong & McDowell, 2018), where nascent occupations are cultivated (Atherton et al, 2017) and where hybrid professional roles across occupational boundaries develop (Colley & Guéry, 2015).…”
Section: Professional Identitymentioning
confidence: 99%